Social welfare reforms in Serbia – undelivered welfare for able-bodied beneficiaries - Perišić, Natalija (Ревија за социјална политика/Journal of Social Policy, 2012)
In Serbia, transition from socialism has had profounding effects in the social welfare sector, all the way during the 1990s and especially after 2000. Changes in the sector have been of legislative and normative nature, but also of ideological and paradigmatic one. And while the irreversibility of the trajectory of changes seems to be out of the question, some important topics have not been put into the agenda, and even if put, solutions to them have not been always straightforward. On the one hand, objectives the society tries to pursue with and within its social welfare system, are those in terms of social inclusion of its beneficiaries, with simultaneous prevention and reduction of social exclusion of its most vulnerable citizens. On the other hand, measures with a view to its effectuating have been largely ineffective, either due to their inappropriate design or incomplete implemenation. This paper is structured around the theoretical background on needs, their interpretation and translation into social rights. Social welfare reforms in the national context are analyzed in the central part of the paper. The emphasis is on the reform of social welfare benefits, more precisely, social welfare benefit in cash (novčana socijalna pomoć), beneficiaries thereof and the exit strategies designed. The objective is to analyze advantages and disadvantages of the social welfare reform concept deployed, and to argue in favour of its transformation and redesign. The research is positioned within the qualitive analytical framework.
Keywords: social welfare; reforms; activation; beneficiaries; benefits